Giant anisotropic thermal expansion actuated by thermodynamically assisted reorientation of imidazoliums in a single crystal - Zi-Shuo Yao (Nature Portfolio, 2019)
Designing materials with large thermal expansion is highly desirable to fabricate microscale devices. The authors report unusually large anisotropic negative and positive thermal expansion in a simple crystalline material, through temperature-driven orientation of imidazole cations acting as molecular wheels.